2021
DOI: 10.1080/02705060.2021.1969295
|View full text |Cite
|
Sign up to set email alerts
|

Variation of water quality parameters and correlation among them and fish catch per unit effort of the Tono Reservoir in Northern Ghana

Abstract: Water quality is essential for fish survival and growth in reservoirs. However, little information is known about the water quality status and its relation with fish production in the Tono Reservoir. This study sought to assess water quality parameters and examine association among them as well as determine the correlation between the water quality parameters and fish catch per unit effort of the Tono Reservoir. A three-level stratified sampling was adopted and samples were collected on a monthly basis. Water … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Within a riverine ecosystem, the abundance of a species changes with seasonal variations in physicochemical properties (Sharma et al2016;Whitfield 1994;Harris and Cyrus 1995;Garcia et al2003). Many researchers in the past have focused on the importance of physicochemical and ecological parameters for outlining the abundance and diversity of fish, prawns and other crustaceans (Martino and Able 2003;Varadharajan et al 2012;Shah and Pandit 2013;Lobato et al 2020;De Sousa et al 2020;Akongyuure et al 2021;Fadlaoui et al 2021;Rathnayake et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Within a riverine ecosystem, the abundance of a species changes with seasonal variations in physicochemical properties (Sharma et al2016;Whitfield 1994;Harris and Cyrus 1995;Garcia et al2003). Many researchers in the past have focused on the importance of physicochemical and ecological parameters for outlining the abundance and diversity of fish, prawns and other crustaceans (Martino and Able 2003;Varadharajan et al 2012;Shah and Pandit 2013;Lobato et al 2020;De Sousa et al 2020;Akongyuure et al 2021;Fadlaoui et al 2021;Rathnayake et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…in rise in turbidity (Halder et al, 1990;Islam et al, 2021), and high values occurred during summer due to lack of rain, runoff and flood water as well as gradual settling of suspended particles (Saxena & Saksena, 2012). Rahman (1992) suggested that productive water bodies have a transparency of no more than 0.4 m. similar seasonal trends were found in the Tono reservoir (Akongyuure & Alhassan, 2021), Raipur reservoir (Saxena & Saksena, 2012) and Sardar Sarovar reservoir (Koushlesh et al, 2022).…”
Section: Discussionmentioning
confidence: 71%
“…Transparency was recorded maximum in 1.85 ± 0.33 m in the pre‐monsoon season and 1.1 ± 0.5 m the monsoon season, which indicates the rapid increase in suspended matter (silt, clay and organic matter) and sediment from the catchment areas during the monsoon season resulting in rise in turbidity (Halder et al, 1990; Islam et al, 2021), and high values occurred during summer due to lack of rain, runoff and flood water as well as gradual settling of suspended particles (Saxena & Saksena, 2012). Rahman (1992) suggested that productive water bodies have a transparency of no more than 0.4 m. similar seasonal trends were found in the Tono reservoir (Akongyuure & Alhassan, 2021), Raipur reservoir (Saxena & Saksena, 2012) and Sardar Sarovar reservoir (Koushlesh et al, 2022).…”
Section: Discussionmentioning
confidence: 76%
“…Water quality is essential for drinking water, irrigation, fish farming, recreation, and other uses that require the storage of water. Physical and chemical limnology determines water quality, which comprises all physical, chemical, and biological aspects of water that affect its wise use [ 1 , 2 ]. Due to over-exploitation of water supplies and poor waste disposal techniques, the quality of surface water has degraded in metropolitan areas.…”
Section: Introductionmentioning
confidence: 99%